PENGARUH PERTUMBUHAN PERUSAHAAN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2016-2019 - Risky Mulyani; Elfreda Aplonia Lau; Rina Masithoh Haryadi (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2022)
This study aims to determine and analyze the effect of firm growth, profitability and firm size on firm value with capital structure as an intervening variable in property and real estate sub-sector companies listed on the stock exchange 2016-2019. The theoretical basis used in this research is financial management, especially company growth, profitability, company size, company value and capital structure. The analytical tool used in this study is Multiple Linear Regression and Path Analysis The results showed that the variable company growth, firm size had a significant negative effect on capital structure & firm value, profitability had a significant positive effect on capital structure & firm value, capital structure had a significant positive effect on firm value, firm growth, profitability, firm size simultaneously had a positive effect. Significant to the value of the company through the capital structure.